Major trauma in older persons. Issue 5 (23rd June 2018) - Beck, B; Cameron, P; Lowthian, J; Fitzgerald, M; Judson, R; Gabbe, B J
Abstract: Background: Globally, populations are ageing, creating challenges for trauma system design. Despite this, little is known about causes of injury and long-term outcomes in older injured patients. This study aims to describe temporal trends in the incidence, causes and functional outcomes of major trauma in older adults. Methods: The population-based Victorian State Trauma Registry was used to identify patients with major trauma aged 65 years and older with a date of injury between 1 January 2007 and 31 December 2016. Temporal trends in population-based incidence rates were evaluated. Functional outcome was measured using the Glasgow Outcome Scale – Extended. Results: There were 9250 older adults with major trauma during the study period. Low falls were the most common mechanism of injury (62·5 per cent), followed by transport-related events (22·2 per cent) and high falls (9·5 per cent). The number of patients with major trauma aged 65 years and older more than doubled from 2007 to 2016, and the incidence increased by 4·3 per cent per year (incidence rate ratio 1·043, 95 per cent c.i. 1·035 to 1·050; P < 0·001). At 12 months after injury, 41·8 per cent of older adults with major trauma had died, and 52·2 per cent of those who survived to hospital discharge were not living independently. Conclusions: The number and proportion of older adults with major trauma are increasing rapidly and this will impact on trauma system design. Given the poor long-term outcomes, there needs to be greater emphasis on ensuring that appropriate interventions are targeted to the right patients and enhanced efforts in primary prevention. Graphical Abstract: A retrospective review of older adult (aged 65 years and older) major trauma patients injured between 2007 and 2016 was performed. The results showed a more than doubling of the number, and an increase in the proportion of major trauma patients aged 65 years and older from 25 per cent in 2007 to 37 per cent in 2016. At 12 months post injury, 42 per cent of older adult major trauma patients had died, and of those that survived to hospital discharge, 52 per cent were not living independently.